2009
DOI: 10.1021/jp808260b
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Equilibria of Bulged Sites in Duplex DNA Studied by EPR Spectroscopy

Abstract: Conformational flexibility in nucleic acids provides a basis for complex structures, binding, and signaling. One-base bulges directly neighboring single-base mismatches in nucleic acids can be present in a minimum of two distinct conformations, complicating the examination of the thermodynamics by calorimetry or UV-monitored melting techniques. To provide additional information about such structures, we demonstrate how electron paramagnetic resonance (EPR) active spin-labeled base analogues, base-specifically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 59 publications
0
12
0
Order By: Relevance
“…It is possible that the presence of an internal mismatch skews the conformation of the duplex, thus generating a greater signal shift. Smith and co‐workers found that one‐base bulges in the position proximal to a mismatch can be present in several conformations that easily interconvert 13. It is our hypothesis that various conformations surrounding the internal two‐base mismatch can influence the waters of hydration and thus lead to a greater radian shift when compared to complementary strands.…”
Section: Kd Values Of Free‐solution Bsi and Surface‐immobilized Bsi Wmentioning
confidence: 79%
“…It is possible that the presence of an internal mismatch skews the conformation of the duplex, thus generating a greater signal shift. Smith and co‐workers found that one‐base bulges in the position proximal to a mismatch can be present in several conformations that easily interconvert 13. It is our hypothesis that various conformations surrounding the internal two‐base mismatch can influence the waters of hydration and thus lead to a greater radian shift when compared to complementary strands.…”
Section: Kd Values Of Free‐solution Bsi and Surface‐immobilized Bsi Wmentioning
confidence: 79%
“…The fluorescent nucleoside is sensitive to its microenvironment and is able not only to detect mismatches, but also to identify the mismatched base [28,29]. The bifunctionality of the spectroscopic probe allows, for the first time, the use of the same nucleic acid sample for both EPR and fluorescence spectroscopies and has been applied for the study of the conformation and dynamics of hairpin loops [30,31] and the folding of a DNA aptamer that binds cocaine [32].…”
Section: Rigid Nitroxide Spin Label ç: a Fluorophore In Disguisementioning
confidence: 99%
“…SDSL studies of DNAs are closely parallel and mutually beneficial to investigations of RNA. Interested readers may consult a 2008 review article,12 as well as many excellent recent publications 41–48…”
Section: Sdsl For Studying Nucleic Acidsmentioning
confidence: 99%